UTILISATION OF CRAYFISH WASTE AND POULTRY OFFAL AS REPLACEMENT FOR FISH MEAL IN CHICKEN DIET (2014)
The escalating cost of dietary protein ingredients necessitates the search for alternatives in poultry production. The inclusion of Crayfish Waste (CW) and Poultry Offal (PO) in chicken feeds could reduce the cost of dietary proteins. The study evaluated the utilisation of CW and PO as dietary protein sources for chicken production. Four experiments were conducted in a completely randomized design using three replicates of 10 birds each. Experiment I involved feeding of diets containing 100%, 75%, 50%, 25% and 0% Crayfish Waste Meal (CWM) as replacement for Fish Meal (FM) to 150 Day-Old Broiler Chicks (DOBC) at starter and finisher phases. In Experiment II, five diets in which Poultry Offal Meal (POM) replaced FM at 100%, 75%, 50%, 25% and 0% were fed to 150 DOBC at starter and finisher phases. In each of experiments III and IV, 180 DOBC and point-of-lay birds were respectively fed with broiler (starter and finisher) and layer diets containing CWM and POM as follows: 100% FM (control), 0:100(2), 25:75(3), 50:50(4), 75:25(5) and 100:0(6). The experiments lasted 9 and 13 weeks respectively. Parameters determined for birds included Crude Protein (CP), Ether Extract (EE), Crude Fibre (CF) and Energy of test ingredients, Body Weight Gain (BWG), Dry Matter Intake (DMI), Feed Conversion Ratio (FCR), Protein Efficiency Ratio (PER), Carcass Characteristics (CC), Blood Urea (BU), Total Protein (TP), Packed Cell Volume (PCV), Haemoglobin (Hb), weekly egg production and egg external parameters, using standard methods. Data were analyzed using descriptive statistics and ANOVA. The CWM contained 35.0%CP, 12.9% CF, 3.9% EE, 1454 Kcal/kg ME. The POM contained: 51.9%CP, 1.8%CF, 6.2% EE, 2600Kcal/kg and FM; 65.1CP, 0.8CF, 6.0EE and 2860Kcal/kg. In Experiment I, BWG, DMI, FCR, and PER were not significantly different at the starter and finisher phases, respectively. In Experiment II, BWG, DMI, and FCR were similar among treatments at the starter phase. However at the finisher phase, BWG was significantly higher (p<0.05) for 75:25 broilers (977.5g) than others while DMI, FCR and PER were similar. At the starters phase of POM and CWM combinations, the DMI for Diet 5 (1.41kg) and 6 (1.18kg) were significantly (p<0.05) different. Birds fed diet 5 recorded the highest BWG (811.30g) which was similar to others but significantly (p<0.05) different from diet 6 (634.9g). At the finisher phase, the control birds consumed 2.98kg similar to diets 2 and 5 but differed significantly (p<0.05) from those on diets 3 and 4. The PER and FCR were similar both at the starter and finisher phases. Chicken fed 100% CWM recorded an eviscerated weight of 89.20% which was significantly (p<0.05) better than others. Treatment effects were similar for PCV and Hb. There were significant (p<0.05) differences between treatments for BU and TP. 50%POM:50%CWM (BU) and 75POM:25CWM (TP) differed significantly (p<0.05) from others. Egg external parameters gave similar result except for control which was significantly lower (p<0.05) than 50 POM:50 CWM. Combination of poultry offal meal and crayfish waste meal was successfully used to replace fish meal at 100% level without adverse effect on production